Sociocultural and structural perpetuators of domestic violence in pregnancy: A qualitative look at what South Indian women believe needs to change. Issue 2 (1st February 2018) - D'Silva, Sahana; Frey, Sarah; Kumar, Shuba; Mohanraj, Rani; Manhart, Lisa E.; Kaysen, Debra; Andu, Eaden; Rao, Deepa
ABSTRACT: In India, reported rates of domestic violence rise as high as 31%. Abuse against pregnant women in India is associated with depressive and PTSD symptoms, and poor birth outcomes, yet no evidence-based interventions have been tested on this population. In this cross-sectional qualitative study, we sought perspective on South Indian women's concerns about abuse during pregnancy and what they believed would help. Participants cited economic dependence on husbands and sociocultural structures as factors perpetuating domestic violence. Women also described resilience factors that can protect against abuse. Our participants highlighted a requisite for interventions within health and social systems.